Síntese e caracterização de [2]rotaxanos: uso de eixos moleculares com estações succinamida e oxoalquil-triazol - Weimer, Gustavo Henrique (2022)
The following work presents the synthesis of molecular thread and molecules of rotaxanes containing two stations, succinamide and oxoalkyl-triazole. The synthetic process of the molecular thread was carried out by “click” reactions involving cycloaddition [3+2] of azides and terminal alkynes copper catalyzed (CuAAC), resulting in yields of 55–83%. The formation of rotaxanes molecules was based on the clipping methodology, consisting in a multicomponent reaction with isolated product yields ranging from 8–25%. The synthesized molecules were identified and characterized by 1H and 13C Nuclear Magnetic Resonance (NMR) spectroscopy in one- and two-dimensional experiments, infrared (IR) spectroscopy, thermogravimetric analysis (TGA), liquid chromatography/tandem mass spectrometry (LC-MS/MS), high resolution mass spectroscopy (HRMS), melting point and single crystal X-ray diffraction (SC-XRD), when possible. The [2]rotaxanes molecules were studied by 1H NMR experiments at variable temperatures. Studies carried out with temperatures variations between -20 to 40 °C revealed the position of the macrocycle over the succinamide station at low temperatures is favored and showing a possible shuttling to the oxoalkyl-triazole station with increasing temperature. This event was observed through variations in chemical displacement of the hydrogens present in the molecular thread station, which suffer a shielding effect due to the formation of hydrogen bonds with the macrocycle. The formation of [3]rotaxanes molecules was not observed for the proposed models. Therefore, alteration in the spacer chain of the oxoalkyl-triazole station is not enough to favor the synthesis of [3]rotaxanes molecules.